Моделювання плазмонних властивостей нанокомпозитних матеріалів на основі алмазоподібної вуглецевої плівки та наночастинок срібла - Яремчук, І. Я.; Фітьо, В. М.; Бобицький, Я. В. (Видавництво Львівської політехніки, 2016)
Розраховано оптичні константи алмазоподібної вуглецевої плівки, з диспергованими в неї наночастинками срібла різної форми, за допомогою ефективної теорії Максвелла–Гарнетта. Здійснено моделювання оптичних характеристик нанокомпозитного матеріалу залежно від розміру і форми включень та матеріалу матриці. Optical characteristics of nanocomposite materials have been modeled depends on materials of the nanoparticles and the matrix, the size and shape of nanoparticles. The optical constants of diamond-like carbon films doped with nanoparticles of silver are considered within the framework of the effective theory of Maxwell–Garnett. It is shown that the concentration, size, shape of nanoparticles and the interaction between them affect the value of the complex effective refractive index of the nanocomposite and are crucial for provision of maximum absorption peak (plasmon peak) and the width of the absorption spectrum. The modeling of the optical properties of the diamond-like carbon film doped by silver nanoparticles with spheroidal shape was provided. In this case the plasmon peaks are shifted to longer wavelengths and broadened. In addition, additionale absorption peaks appear. It is demonstrate that renormalized Maxwell–Garnett effective theory, which includes size effect and near field interaction between nanoparticles, can be successfully applied to describe the optical properties of silver diamond-like carbon nanocomposite films with the high concentration of Ag nanoparticles. The obtained results suggest as well that a random mixture consisting of a diamond-like carbon film with embedded isolated silver inclusions is promising material for the fabrication of tunable nanocomposites that could used in different optical systems employing surface plasmon resonance.
Modelling of the plasmonic properties of nanocomposite materials based on diamond-like carbon film and silver nanoparticles
Keywords: нанокомпозит; ефективна теорія Максвелла–Гарнетта; плаз- монний резонанс; nanocomposite; effective theory Maxwell–Garnett; plasmon resonance